(untitled) (Raparin Journal of Humanities (RJH), 2023)
Al_Hajjaj considers argumentation an essential topic of modern linguistics، It is one of the linguistic activities on which the speaker، writer or orator depends. In modern linguistics studies، Al _Hajjaj has become an independent theory and is considered one of the deliberative investigations. It also represents a prominent and fundamental role in various sciences such as (philosophy، logic، politics and law... etc) and he has permanent presence among those sciences. In these few pages، I tried to stand on the meaning and concept of Al_Hajjaj from the linguistic and idiomatic stand points، and then stand on its relationship to his conceptual field. as it showed for Al_Hajjaj from the moral side as well as the bilateral relationship between each of the terms.